Effect of pawpaw seed meal supplementation on productivity, mortality and carcass characteristics of indigenous Venda chickens raised in closed confinement - Mosehlana, Solly Ynkwane (My University, 2013)
A nutritional experiment was conducted to determine the effect of pawpaw seed meal supplementation on productivity, mortality and carcass characteristics of indigenous Venda chickens raised in closed confinement. Supplementation levels of 0, 50, 100, 150 and 200 g of pawpaw seed meal per kg DM feed were used in a completely randomised design having five replications with 10 birds per replication. Pawpaw seed meal supplementation had no effect (P>0.05) on growth rate, live weight, nitrogen retention and diet DM digestibility of Venda chickens aged one to seven weeks. Similarly, pawpaw seed meal supplementation had no effect (P>0.05) on feed intake, growth rate, live weight, diet DM digestibility, and carcass, breast, thigh, drumstick, wing, gizzard, liver, heart and fat pad weights and also on meat juiciness and flavour of female Venda chickens aged eight to 13 weeks. However, pawpaw seed meal supplementation improved (P<0.05) feed intake, feed conversion ratio and metabolisable energy of Venda chickens aged one to seven weeks. Similarly, pawpaw seed meal supplementation improved (P<0.05) feed conversion ratio, metabolisable energy, nitrogen retention and meat juiciness of female Venda chickens aged eight to 13 weeks. Mortality of indigenous Venda chickens fed diets supplemented with pawpaw seed meal was reduced from 20 to 0 % (P<0.05) as compared to those of chickens on diets without pawpaw seed meal supplementation. Growth rate, live weight, metabolisable energy and nitrogen retention of indigenous Venda chickens aged one to seven weeks were optimized at different pawpaw seed meal supplementation levels of 133, 143, 101 and 133 g/kg DM feed, respectively. Similarly, growth rate, live weight, metabolisable energy and nitrogen retention of female Venda chickens aged eight to 13 weeks were optimized at different pawpaw seed meal supplementation levels of 54, 87, 69 and 177 g/kg DM feed, respectively. Results of the present study showed no single dietary pawpaw seed meal supplementation level for all production variables. It is concluded that pawpaw seed meal supplementation can reduce mortality of indigenous Venda chickens.
Thesis (M.Sc. (Animal Production)) -- University of Limpopo, 2013
Keywords: Chickens; Dietary supplements; Growth rate; Pawpaw seed meal; Chickens; Chickens -- Hatcheries; Dietary supplements; Poultry -- Housing; Poultry -- Feeding and feeds